THE TRANSFORMATION PROBLEMS OF TRANSLATION FROM ENGLISH PROVERBS INTO UZBEK LANGUAGES - Nafisa Хаjibaevna, Elmuratova (Recent scientific discoveries and methodological research, 2025)
This article depend on the translation of English children's fiction into Uzbek considers the national-cultural and universal features of proverbs in English and Uzbek in the problems of transformation. Some aspects of the proverb also reveal in detail the problems of the translation of proverbs today. Since there are different types of translation, the translation is interpreted in accordance with its own. Special attention is paid to the types of translation of the proverb. This translation of English children's fiction into Uzbek presents the conclusions of famous writers and scientists, as well as the work carried out on proverbs in folk oral literature, and the role and importance of proverbs in human life. When we compared proverbs in different languages, we identified differences and similarities between them.